The Dermis fat graft: Retrospective case series from Pakistan: Doi: 10.36351/pjo.v41i4.2038 - Sumeya Ali Khan; Manzoor, Amna; Fariha Taimur; Saad Ullah; Murtaza Sameen (Pakistan Journal of Ophthalmology, 2025)
The case series was conducted at Department of Orbit and Oculoplastics, Alshifa Trust Eye Hospital, Rawalpindi, from January 2023 to July 2024. It included 25 eyes of 25 patients who underwent a standardized dermis fat graft transplantation for anophthalmia. There were 15 male patients, and the mean age of study participants was 34.1±12.01. Two out of 25 patients had significant volume loss and were booked for another surgery and 3 had surgical site infection requiring a longer course of antibiotics. All patients reported satisfaction with prosthesis fitting till 6 months of followup. The superior sulcus ,lid position and prosthesis tilt was compared to the fellow eye.Dermis fat graft proved to be a good option for anophthalmic sockets. It can also be used as a primary procedure for obviously pthisical, traumatic globes